2009
DOI: 10.1038/bmt.2009.135
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilia predicts better overall survival after acute graft-versus-host-disease

Abstract: The prognostic significance of eosinophilia after allogeneic hematopoietic SCT (HSCT) and the relationship between eosinophilia and acute GVHD are not well studied. We retrospectively analyzed 201 adult patients who underwent their first allogeneic HSCT. Seventy-three (36%) patients developed eosinophilia within the first 100 days after HSCT. Eosinophilia was observed more frequently among those patients with acute GVHD than those without it (48 vs 25%, P ¼ 0.009). However, it was associated with milder acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…To our knowledge, four studies indicate better outcome after allo-HCT if eosinophilia is present (3)(4)(5)(6). Two previous studies reported that eosinophilia after allo-SCT correlated with lower relapse rates (3,5), and three studies showed that eosinophilia after allo-SCT was associated with lower NRM (4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To our knowledge, four studies indicate better outcome after allo-HCT if eosinophilia is present (3)(4)(5)(6). Two previous studies reported that eosinophilia after allo-SCT correlated with lower relapse rates (3,5), and three studies showed that eosinophilia after allo-SCT was associated with lower NRM (4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…The median time of onset of Eo+ was 47 days (range: 21-1,026) after allo-HCT, but eosinophilia tended to occur later after CBT (81.5 days) than after BMT and PBSCT (42 and 43.5 days, respectively) (p=0.05). The median maximum eosinophil count of Eo+ was 1,403×10 6 /L (range: 516-10,010×10 6 ), and there was no difference among those with BMT, PBSCT, or CBT (1,280, 1,210 and 1,740×10 6 , respectively, p=0.47). Of 144 patients, 51 patients (35%) died during the follow-up period and the median follow-up period of survivors was 1,072 days (range: 129-2,737) after the landmark day.…”
Section: Patient Characteristics and Eosinophiliamentioning
confidence: 99%
See 2 more Smart Citations
“…Although elevated eosinophil counts have been reported in adults with chronic GvHD, no correlation with outcome could be shown [4]. However, in adults with acute GvHD after HSCT, elevated eosinophils were associated with a better overall survival [19]. Frankovich et al [12] have reported an association of asthma and atopic history and non-infectious pulmonary complications after autologous HSCT in pediatric Hodgkin patients [11].…”
Section: Introductionmentioning
confidence: 97%